Application of the Analytical Hierarchy Process in the management of private ambulance care systems in three selected European countries: a strategic decision-making framework - Jalal Rezaei; Roya Azouji; Mina Azouji; Hamzeh Ghorbani; Hamzeh Ghorbani (Frontiers in Public Health)
Private ambulance services play a vital role in healthcare systems across Europe, supplementing public emergency services and providing essential medical transportation. However, managing these services presents significant challenges, including resource allocation, regulatory compliance, service quality, technological integration, workforce management, and financial sustainability. This study employs the Analytical Hierarchy Process (AHP) as a strategic decision-making tool to optimize the management of private ambulance services in Germany, Spain, and the United Kingdom. To achieve this, data were collected from 20 participants across the three countries (Germany: 7, Spain: 6, United Kingdom: 7), comprising ambulance service administrators, emergency medical personnel, and regulatory experts. A purposive sampling method was used to ensure the inclusion of key stakeholders with direct experience in the sector. Participants completed structured questionnaires involving pairwise comparisons of key decision criteria. Results reveal that Regulatory Compliance is the highest priority across all countries (Germany: 0.25, Spain: 0.22, UK: 0.20), followed by Service Quality, which is particularly emphasized in the UK (0.22) and Germany (0.20). Technological Integration is important in Spain (0.20), reflecting the need for advancements in underserved areas. While Workforce Management and Financial Sustainability rank slightly lower, they remain critical for operational efficiency. The study highlights country-specific challenges and regulatory differences and provides actionable recommendations for optimizing resource allocation, improving service quality, and ensuring compliance. Despite limitations such as potential biases and a narrow geographic focus, the findings offer valuable insights for refining management practices and enhancing the sustainability of private ambulance services across Europe.